Development Of Professional Competence Of Students Based On Mathematics Training Through Software Tools (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this this article given some recommendations to teach you how to develop a software product using the Python programming language. In addition, interdisciplinary integration has been shown to be important in preparing future mathematicians for professional careers.